Keratitis caused by Nocardia farcinica in a contact lens wearer - Shaymaa Hegazy; Tung Phan (Infectious Medicine, 2022)
Bacterial keratitis is an infection of the cornea. This kind of infection can progress quickly and if left untreated, it can eventually cause complete blindness. While Staphylococcus aureus and Pseudomonas aeruginosa are most commonly responsible for this type of infection in the United States, Nocardia spp. is rarely encountered. Here we describe an interesting case of Nocardia farcinica keratitis in a 31-year-old male patient having an extended wear of contact lenses. The patient presented at the emergency department with irritation, foreign body sensation, redness, and pain of his left eye. Nocardia farcinica was isolated from a corneal scraping specimen, and determined by sequencing a region of 16S rRNA gene. The patient had antimicrobial therapy with good improvement. We highlight the important role of Nocardia farcinica in causing keratitis, and its accurate and timely diagnosis is needed to avoid poor visual outcomes.